Cyclic and Square-Wave Voltammetry at Diffusionally Asymmetric Microscopic and Nanoscopic Liquid-Liquid Interfaces: A Simple Theoretical Approach - Molina, A; Laborda, E; Compton, R (2014)
The theoretical modeling of reversible ion transfers across liquid-liquid interfaces supported at micro/nanocapillaries is developed by means of a simple, approximate analytical approach. A very simple analytical solution is obtained for any multipulse technique and applied to the case of the two most widely used voltammetric techniques: cyclic and square-wave voltammetries. The analytical results fully describe the shape and position of the voltammograms as well as the effect of the key variables of the system: capillary size, time scale of the experiment, and ion diffusion coefficients and bulk concentrations. Their influence is analyzed and quantified with simple equations that immediately enable the determination of the ion-transfer formal potential. © 2014 American Chemical Society.